Government expenditure on health and maternal mortality in México: A spatial‐econometric analysis. (7th January 2019) - Pérez‐Pérez, Eduardo; Serván‐Mori, Edson; Nigenda, Gustavo; Ávila‐Burgos, Leticia; Mayer‐Foulkes, David
Summary: Objective: To assess the relationship between government expenditure on maternal health (GE) and maternal mortality (MM) in Mexican poor population between 2000 and 2015 in the 2457 Mexican municipalities. Methods: Using administrative data, we performed the analysis in three stages: First, we tested the presence of selection bias in MM. Next, we assessed the presence of spatial dependence in the incidence and severity of MM. Finally, we estimated a spatial error model considering the correction of estimates for the spatial dependence and selection bias assessed before. Results: MM and GE were not randomly distributed throughout the Mexican territory; the most socially vulnerable municipalities exhibited the highest levels of MM severity but the lowest levels of GE and available human and physical resources for maternal health; the incidence of MM was independent of GE; elasticity of GE‐severity in MM was −4% ( P  < 0.01). Conclusions: Resource allocation for maternal health must move towards a more comprehensive vision, and efforts to achieve an effective delivery of universal health services must improve, particularly regarding the most vulnerable municipalities.